Factors associated with knowledge and attitude towards adult cardiopulmonary resuscitation among healthcare professionals at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia: an institutional-based cross-sectional study - Abraham Tarekegn Mersha; Amare Haile Kiros Gebre Egzi; Hailu Yimer Tawuye; Nigussie Simeneh Endalew (BMJ Open)
Objective This study was conducted to assess the factors associated with knowledge and attitude towards adult cardiopulmonary resuscitation (CPR) among health professionals at the University of Gondar Hospital, Northwest Ethiopia.Study design An institutional-based cross-sectional study was conducted from 15 February to 15 March 2018. Both bivariable and multivariable logistic regression analyses were used to identify factors associated with knowledge and attitude level of health professionals towards CPR. Variables with a p value less than <0.2 in the bivariable analysis were fitted into the multivariable analysis. In the multivariable analysis, variables with a p value <0.05 were considered statistically significant.Setting University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia.Participants A total of 406 health professionals (physicians, nurses, anaesthetists, health officers and midwives) were included.Results Among the study participants, 25.1% (95% CI 21.2 to 29.3) had good knowledge and 60.8% (95% CI 55.9 to 65.5) had good attitude towards adult CPR. Work experience (adjusted OR (AOR): 5.02, 95% CI 1.25 to 20.20), number of work settings (AOR: 6.52, 95% CI 2.76 to 15.41), taking CPR training (AOR: 2.76, 95% CI 1.40 to 5.42), exposure to cardiac arrest case (AOR: 2.16, 95% CI 1.14 to 4.07) and reading CPR guidelines (AOR: 5.57, 95% CI 2.76 to 11.20) were positively associated with good knowledge. Similarly, taking CPR training (AOR: 1.74, 95% CI 1.42 to 1.53) and reading CPR guidelines (AOR: 2.74, 95% CI 1.55 to 4.85) were positively associated with good attitude.Conclusions The level of knowledge and attitude of health professionals towards adult CPR was suboptimal. Health professionals who were taking CPR training and reading CPR guidelines had good knowledge and attitude towards CPR. In addition, work experience, number of work settings and exposure to cardiac arrest case had a positive association with CPR knowledge. Thus, providing regular CPR training and work setting rotations is highly crucial.